The sunset land; or, The great Pacific slope. - Todd, John, 1800-1873. (Boston, Lee and Shepard, 1870)
John Todd (1800-1873), a Congregationalist clergyman in Pittsfield, Massachusetts, wrote widely and published several religious magazines. The sunset land (1870) contains Todd's experiences as a visitor to California in the mid 1860s, with essays on the state's history, climate, agricultural products, and geology; gold mining; the Calaveras redwoods; and Yosemite Valley. He devotes a chapter to Mormonism and what he believes to be its inevitable decline; another, to the triumph of the transcontinental railroad; and a third, to the city of San Francisco.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; Mormon Church; Mines and mineral resources -- California; Ethnic groups -- California; Agriculture -- California; Business -- California